Pembentukan Pokdarwis dalam Mendorong Ekowisata dan Pelestarian Lingkungan di Desa Erelembang: Pengabdian - Rahmat, Abdul; Muhammad Raihan; Ashfar, Nurul Miftah Rizqy; Syam, Afdhal Hidayat; Maulidan, Muhammad Alif; Latif, Nur Ismy (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The formation of the Tourism Awareness Group (Pokdarwis) is a strategic step to promote ecotourism development and environmental conservation in Erelembang Village, Tombolo Pao District, Gowa Regency. This village has abundant natural potential, such as agriculture, pine forests, and scenic rice terraces, but it has not been optimally utilized. This service project employs a participatory approach by involving the local community in the planning, implementation, and evaluation of tourism development activities through the